PENERAPAN SISTEM INFORMASI KELOLA UI DALAM MENUNJANGBISNIS PROSES PADA DIREKTORAT PENDIDIKAN PUSAT ADMINISTRASI UNIVERSITAS (PAU)UNIVERSITAS INDONESIA - Anza, Fikri Akbarsyah; Cahyaningsih, Tri (UI Scholars Hub, 2019)
This study discusses the implementation of Information System Kelola UI in the University of Indonesia, especially in the Unit of the Directorate of Education and Faculties related to the Directorate of Education through system information Kelola UI. The aim of this study is to explain how the implementation of Information System Kelola UI at the Directorate of Education, University Central Administration Universitas Indonesia (PAUI), related to the business process at Directorate of Education PAUI. This research uses quantitative approach method with explanative design. The data are collected through the questionnaires, in-depth interviews and literature studies. The analysis of this study is using best practice COBIT 4.1. This research focuses on 3 domains of COBIT 4.1: Plan & Organize (PO), Acquire & Implement (AI), and Deliver & Support (DS). The results showed that overall implementation of information systems Kelola UI has been running well and as expected at Directorate of Education PAUI. Common problems that still occurred was Human Resources, information update, and low concern in system evaluation.